Efektivitas Hukum Humaniter Dalam Menghadapi Taktik Perang Asimetris Kontemporer - Putra, Deki Rayusyah; Negara, Agung Perwira; Susilo, Tarsisius; Adriono, Rudi; Setyoko, Budi (Jurnal sosial dan sains, 2025)
The transformation of global conflict architecture over the past decade reflects a significant shift toward non-conventional or asymmetric warfare, characterized by the involvement of non-state actors, guerrilla tactics, cyber infiltration, and the deployment of autonomous weapon systems. This type of warfare has blurred the distinction between combatants and civilians, thereby complicating the application of core principles of International Humanitarian Law (IHL), such as distinction, proportionality, and precaution. This study aims to evaluate the effectiveness and adaptive capacity of IHL in addressing the challenges posed by contemporary asymmetric warfare. The research employs a normative juridical approach using an evaluative-reflective model based on normative gap analysis, complemented by case studies of conflicts in Syria and Yemen. The findings reveal a structural disparity between universal legal norms and operational practices in the field, where violations of IHL principles frequently occur in the absence of effective accountability mechanisms. This study recommends reforming international legal instruments through the integration of adaptive legal principles, the inclusion of non-state actors, and the development of technology-based legal monitoring systems. Such an approach is essential to reinforce IHL systems to be more contextual, dynamic, and responsive to evolving forms of armed violence in the contemporary era.